2018
DOI: 10.1002/er.4184
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure effect on ion conduction in composite electrolyte

Abstract: Summary In this work, the microstructure of composite electrolyte is reconstructed by randomly packing cubes, and the charge transport process is simulated to calculate the effective conductivity ratio σeff/σ0 of the designated conducting phase. Effects of the volume fraction and the electrolyte particle size on σeff/σ0 are also examined. Results show that σeff/σ0 is independent of the particle size but sensitive to its volume fraction. Finally, a new formula is proposed to quickly predict the σeff/σ0 of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…solution and dry membrane were employed to elucidate the molecular-level interactions in the membrane assembly. [16] As shown in Figure S1-S2 , Compared with the FT-IR spectrum of RN,t he Nafion-Bi 12 -3 %a nd Nafion-Bi 12 -5 %m embranes displayed the characteristic vibrations of {H 6 Bi 12 O 16 }clusters, further certifying the composition of Nafion/{H 6 Bi 12 O 16 } hybrid membranes.M eanwhile,b yc omparing the FT-IR spectra results ( Figure S3), it can be also observed that as the content of the added {H 6 Bi 12 O 16 }c luster increases,t he broad peak at 3480 cm À1 (OH asymmetric stretching vibration) shifts towards al ower wavenumber,i ndicating the hydrogen bonding interaction between the Nafion and the bismuth oxygen cluster molecules.A ss hown in Figure S4, the Zeta potential measurements illustrate the existence of electrostatic interaction between the positively charged {H 6 Bi 12 O 16 } clusters and the negatively charged Nafion side chains.T he above results indicated that {H 6 Bi 12 O 16 }c lusters can be successfully hybridized into the Nafion membranes through electrostatic and hydrogen-bonding interactions. Figure 1a and S5-S6 exhibited the scanning electron microscopy (SEM) images of the cross-sectional morphology for RN,N afion-Bi 12 -3 %, and Nafion-Bi 12 -5 %m embranes, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…solution and dry membrane were employed to elucidate the molecular-level interactions in the membrane assembly. [16] As shown in Figure S1-S2 , Compared with the FT-IR spectrum of RN,t he Nafion-Bi 12 -3 %a nd Nafion-Bi 12 -5 %m embranes displayed the characteristic vibrations of {H 6 Bi 12 O 16 }clusters, further certifying the composition of Nafion/{H 6 Bi 12 O 16 } hybrid membranes.M eanwhile,b yc omparing the FT-IR spectra results ( Figure S3), it can be also observed that as the content of the added {H 6 Bi 12 O 16 }c luster increases,t he broad peak at 3480 cm À1 (OH asymmetric stretching vibration) shifts towards al ower wavenumber,i ndicating the hydrogen bonding interaction between the Nafion and the bismuth oxygen cluster molecules.A ss hown in Figure S4, the Zeta potential measurements illustrate the existence of electrostatic interaction between the positively charged {H 6 Bi 12 O 16 } clusters and the negatively charged Nafion side chains.T he above results indicated that {H 6 Bi 12 O 16 }c lusters can be successfully hybridized into the Nafion membranes through electrostatic and hydrogen-bonding interactions. Figure 1a and S5-S6 exhibited the scanning electron microscopy (SEM) images of the cross-sectional morphology for RN,N afion-Bi 12 -3 %, and Nafion-Bi 12 -5 %m embranes, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…Fourier‐transformed infrared (FTIR) spectra of recast Nafion (RN), Nafion‐Bi 12 ‐3 %, Nafion‐Bi 12 ‐5 % in casting solution and dry membrane were employed to elucidate the molecular‐level interactions in the membrane assembly [16] . As shown in Figure S1–S2, Compared with the FT‐IR spectrum of RN, the Nafion‐Bi 12 ‐3 % and Nafion‐Bi 12 ‐5 % membranes displayed the characteristic vibrations of {H 6 Bi 12 O 16 } clusters, further certifying the composition of Nafion/{H 6 Bi 12 O 16 } hybrid membranes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, proton conductors are promising candidates for SOFC electrolytes since they have high protonic conductivity at low temperatures [ 20 , 21 ]. BCZYs from cerate and zirconate families are considered promising perovskite electrolytes because, at low temperatures, they exhibit high proton conductivity [ 20 , 22 , 23 ]. Ni et al observed that barium cerate (BaCeO 3 ) electrolytes exhibit high ionic conductivity that can be enhanced to 10 −2 Ω −1 cm −1 by (15–20%) doping of yttrium.…”
Section: Introductionmentioning
confidence: 99%